1994
DOI: 10.1159/000097160
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nitric Oxide in Control of Growth Hormone Release in the Rat

Abstract: Previous experiments in this and other laboratories have revealed that nitric oxids (NO) plays a role in controlling the release of corticotropin-releasing hormone (CRH) and luteinizing-hormone-releasing hormone (LHRH). Therefore, we have investigated its role in control of growth hormone (GH) release in conscious rats by microinjecting NG-monomethyl-L-arginine (NMMA), an inhibitor of NO synthase (NOS), into the third ventricle (3V) of conscious, freely moving castrate male rats. An initial blood sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

1995
1995
2001
2001

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 0 publications
1
21
0
1
Order By: Relevance
“…Our results are in agreement with theirs and indicate that NO has precious little effect on basal LH release from hemipituitaries; however, the paracrine actions of gonadotropes on prolactin secretion may be brought about by NO. From these studies, it is apparent that NO has important effects on the secretion of pituitary hormones not only by altering release of releasing hormones from the hypothamus but also by actions on the gland itself. In the case of prolactin, we have reported that injection of NMMA into the third brain ventricle had no effect on basal pulsatile prolactin release, but that it completely blocked the stimulation of prolactin release induced by injection into the third ventricle of interleukin-1 a subunit (IL-la) (9). We believe that this represents an action on the hypothalamus to suppress the secretion of prolactinreleasing factors induced IL-la.…”
Section: Discussionmentioning
confidence: 96%
“…Our results are in agreement with theirs and indicate that NO has precious little effect on basal LH release from hemipituitaries; however, the paracrine actions of gonadotropes on prolactin secretion may be brought about by NO. From these studies, it is apparent that NO has important effects on the secretion of pituitary hormones not only by altering release of releasing hormones from the hypothamus but also by actions on the gland itself. In the case of prolactin, we have reported that injection of NMMA into the third brain ventricle had no effect on basal pulsatile prolactin release, but that it completely blocked the stimulation of prolactin release induced by injection into the third ventricle of interleukin-1 a subunit (IL-la) (9). We believe that this represents an action on the hypothalamus to suppress the secretion of prolactinreleasing factors induced IL-la.…”
Section: Discussionmentioning
confidence: 96%
“…However, the mechanism by which NO influences GH secretion is still a matter of controversy. Pleiotropic effects on somatotropes increased GHRH secretion [14]and increased [15]or decreased [17]hypothalamic somatostatinergic tone has been postulated. Our data showing that L-NAME can block completely cGH secretion stimulated by GHRH are compatible with the hypothesis that NO acts by stimulating somatostatin release and/or by inhibiting cGH release at the pituitary level.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, either facilitatory or inhibitory actions of NO on basal and/or stimulated GH release have been reported in vivo and in vitro [13, 14, 15]. Other data have indicated that appropriate NO supply is essential for full efficacy of different GH stimulators, such as GHRH, GHRP-6 or kainic acid [16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…NOergic neurons stimulate the release of a number of polypeptides from the hypothalamus including luteinizing hormone-releasing hormone (LHRH) (3), corticotropinreleasing hormone (4), somatostatin (5), growth hormonereleasing hormone (6), and prolactin-releasing factors (7).…”
mentioning
confidence: 99%